2020
DOI: 10.1021/acsbiomaterials.0c00776
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Chemistries, Growth Mechanisms, and Antibacterial Properties of Cerium- and Yttrium-Containing Nanoparticles

Abstract: Under the current climate, physicians prescribe antibiotics for treating bacterial infections, and such a limitation to a single class of drugs is disadvantageous since antibiotic-resistant bacteria have adapted to withstanding their stresses. Antibiotic alternatives are sought, and herein metal nanoparticles comprised of the rare earth elements cerium and yttrium were determined to invoke toxicity on methicillin-resistant Staphylococcus aureus (MRSA) and a multi-drug-resistant strain of Escherichia coli (MDR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Wakabayashi [ 94 ] demonstrated that RE ions exhibit antibacterial activity against Staphylococcus aureus and Escherichia coli ( E. coli ) . It has been reported that Ce- [ 95 ], La- [ 96 , 97 ], Y- [ 98 ], Tb- [ 99 ], Dy- [ 100 ], Nd- [ 101 , 102 ], Yb- [ 103 ], Sm- [ 104 ] and Ho-based [ 105 ] nanomaterials possess extensive antibacterial properties and high biocompatibility, making them promising candidates for bone regeneration [ 106 ].…”
Section: Physicochemical Properties and Biological Advantages Of Re Nmsmentioning
confidence: 99%
“…Wakabayashi [ 94 ] demonstrated that RE ions exhibit antibacterial activity against Staphylococcus aureus and Escherichia coli ( E. coli ) . It has been reported that Ce- [ 95 ], La- [ 96 , 97 ], Y- [ 98 ], Tb- [ 99 ], Dy- [ 100 ], Nd- [ 101 , 102 ], Yb- [ 103 ], Sm- [ 104 ] and Ho-based [ 105 ] nanomaterials possess extensive antibacterial properties and high biocompatibility, making them promising candidates for bone regeneration [ 106 ].…”
Section: Physicochemical Properties and Biological Advantages Of Re Nmsmentioning
confidence: 99%
“…It has been reported that the mixed valence states in ceria structures or the reversible conversion of Ce 3+ and Ce 4+ states has strongly been linked to the antioxidant properties of ceriumbased systems. 74 For the claimed antimicrobial activity of Ho@ MS-CeO 2 nanostructures, continuous reversible switching occurred on the ceria surface, which is a distinct property of CeO 2 lattices. 74 Figure 15A shows the XPS spectrum of Ho@ MS-CeO 2 after the antibacterial test, which clearly shows the conversion of ions (Ce 4+ reduced into Ce 3+ ).…”
Section: Mechanism Analysis Of Antibacterial Propertiesmentioning
confidence: 99%
“…74 For the claimed antimicrobial activity of Ho@ MS-CeO 2 nanostructures, continuous reversible switching occurred on the ceria surface, which is a distinct property of CeO 2 lattices. 74 Figure 15A shows the XPS spectrum of Ho@ MS-CeO 2 after the antibacterial test, which clearly shows the conversion of ions (Ce 4+ reduced into Ce 3+ ). Figure 15B shows that the oxygen peak intensities of Ho@MS-CeO 2 have a higher peak intensity (O L ), which evidently specified the presence of more oxygen vacancies.…”
Section: Mechanism Analysis Of Antibacterial Propertiesmentioning
confidence: 99%
“…Since Y 2 O 3 nanoparticles bind to the cell membrane by strong electrostatic forces, they are able to effectively suppress the growth of both Gram-positive and Gram-negative bacteria at a concentration of 100 µg/mL. According to the previous reports on the mechanism of antibacterial action of Y 2 O 3 nanoparticles, yttrium ions may penetrate the cell wall of bacteria and inhibit the growth through down-regulation of enzyme activity, which leads to bacterial cell death [5,31,32]. In contrast to antibiotics, Y 2 O 3 nanoparticles that were synthesized from the leaf extract of Lantana camara (LC) exhibited an excellent inhibitory zone.…”
Section: Antibacterial Activitymentioning
confidence: 99%